RETRACTED: An investigation of corporate social responsibility conformity: The roles of network prominence and supply chain partners - Falcone, Ellie C.; Ridge, Jason W. (Journal of Operations Management, 2024)
Abstract Numerous studies on corporate social responsibility (CSR) indicate that firms adopt CSR practices for various reasons related to their supply chain. However, the necessity to conform to a firm's own industry CSR norm is overlooked. Conforming to one's industry CSR norm—a herding behavior known as CSR conformity —ensures firm in‐group legitimacy and preserves internal resources for core business activities. On the other hand, deviating from industry norms sets a firm apart from its peers, making the firm more appealing to supply chain partners. Motivated by this dilemma, this study draws on middle‐status conformity theory and explores how a firm's network prominence determines its CSR conformity. Panel data analyses of 1650 firm‐year observations reveal an inverse U‐shaped relationship between firm network prominence and its CSR conformity, indicating that firms with a mid‐level network prominence engage in higher CSR conformity. However, the inverse U is flattened when a firm's supply chain partners (and their respective industries) share similar CSR standards, suggesting that a firm can only prioritize its own industry CSR norms if its supply chain partners share a compatible CSR standard. These findings highlight the importance of understanding CSR from an organizational conformity perspective, especially in the context of supply chain network.